Production of a recombinant bacterial lipoprotein in higher plant chloroplasts - Glenz, Karin; Bouchon, Bernadette; Stehle, Thomas; Wallich, Reinhard; Simon, Markus M.; Warzecha, Heribert (Nature biotechnology, 2006)
Little is known about the potential of plastids to accomplish post-translational modifications of foreign proteins. In the present study we generated transplastomic tobacco plants that accumulate the outer surface lipoprotein A (OspA)-the basic constituent of the first generation monovalent human vaccine against Lyme disease. The recombinant OspA exhibits a lipid modification typical for bacteria and induced protective antibodies in mice, demonstrating that functionally active bacterial lipoproteins can be processed in plants.